Measure The Quality of Rice in The Warehouse (Case Study: Bulog Warehouse) - Edy Fradinata; Zurnila Marli Kesuma; Latifah Rahayu (Jurnal Serambi Engineering, 2023)
Abstract This study employs multiple qualitative and quantitative phases of quality assessment at one of Perum Bulog's warehouses. A descriptive qualitative study using observation data collecting and interviews with the quality control team is used. Rice is a need for the people of Indonesia. Perum Bulog is responsible for rice price stability in Indonesia. According to Presidential Instruction No. 3 of 2007 and SNI 6128:2020, rice in Bulog warehouses must adhere to quality criteria. Regarding the quality requirements for the distribution of rice, Bulog performs a quality check on the rice received. Bulog's quality control procedure consists of three stages: the acceptance process, where samples of rice obtained from farmers are taken, and the quality control officer's mini-laboratory sample test inspections. After screening at the receiving stage, the rice will be weighed and then placed in the warehouse with a stapling arrangement system (rice stacking) utilizing key 5. At the rice storage stage, minimal monitoring will be performed periodically, and if the rice is infested with pests, it will be sprayed or fumigated. The last procedure is the exit process, and the warehouse employs the First In First Out approach when customers make purchases.Keywords: rice, warehouse, quality, bulog, price stability